2021
DOI: 10.1016/j.yebeh.2021.108205
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and longitudinal evaluation of cannabidiol (CBD) product use and health among people with epilepsy

Abstract: Recent approval of Epidiolex Ò (pharmaceutical cannabidiol/CBD) for the treatment of Lennox Gastaut syndrome (LGS) and Dravet syndrome highlights a therapeutic efficacy of CBD in the treatment of epilepsy. However, a large number of patients with epilepsy elect to use alternative artisanal CBD products due to cost or access constraints. Despite widespread availability and variety of these artisanal CBD products, studies evaluating their safety or efficacy are rare, making conclusions about clinical utility unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…With many individuals continuing to self-medicate with artisanal cannabis preparations in Australia [4,5,7] and the US [8], contaminants may be unknowingly ingested by many vulnerable individuals suffering chronic illness, including children and adolescents with epilepsy. In a previous study, we collected individual samples of cannabis extracts from families in Australia who were using them to treat their child's epilepsy, and conducted an analysis of cannabinoid and terpenoid content [4].…”
Section: Introductionmentioning
confidence: 99%
“…With many individuals continuing to self-medicate with artisanal cannabis preparations in Australia [4,5,7] and the US [8], contaminants may be unknowingly ingested by many vulnerable individuals suffering chronic illness, including children and adolescents with epilepsy. In a previous study, we collected individual samples of cannabis extracts from families in Australia who were using them to treat their child's epilepsy, and conducted an analysis of cannabinoid and terpenoid content [4].…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, the current manuscript presents a qualitative thematic content analysis of open-ended survey responses detailing the experiences of 808 medicinal cannabis users. Earlier quantitative analyses of data from the present study sample reported significant health benefits associated with medicinal cannabis use ( Schlienz et al, 2020 ; Martin et al, 2021 ; Strickland et al, 2021 ). Schlienz et al (2020) initially found significantly better self-reported quality of life, health satisfaction, and sleep, and significantly lower pain severity, anxiety, and depression among a sample of 808 medicinal cannabis users compared to a control group of 468 patients with similar health issues and demographics who were not medicinal cannabis users.…”
Section: Introductionmentioning
confidence: 55%
“…Finally, Strickland and others (2021) compared a subsample of patients with epilepsy who used cannabidiol (CBD) products ( n = 280) with a control group of individuals with epilepsy who did not use CBD or medicinal cannabis ( n = 138), finding better quality of life and sleep, and lower severity of psychiatric symptoms among the CBD users at baseline. No difference was found in self-reported seizures, though this may indicate a floor effect due to the high proportion ( >40%) of respondents who reported no past-month seizures ( Strickland et al, 2021 ).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations